METODE MUHAMMAD NASHIRUDDIN AL-ALBANI DALAM MENDAIFKAN HADIS: TELAAH KITAB DAIF SUNAN ABU DAUD - Aufi Izzadine; Nur Kholis bin Kurdian; Muhammad Haikal Ali Basyarahil (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
Sunan Abu Dawud is one of the six main hadith books in the Sunni hadith tradition. This book was compiled by Imam Abu Dawud Sulaiman bin al-Ash'ath al-Sijistani in the 3rd century Hijriyah. This book contains hadiths related to Islamic law, arranged based on fiqh chapters. On the other hand, Sheikh Muhammad Nasiruddin al-Albani was a hadith scholar in the 20th century who was famous for his dedication to studying and assessing the authenticity of hadiths contained in classical hadith books, in addition to sahihain. In the context of Daif Sunan Abu Dawud, al-Albani filtered the hadiths contained in the book of Sunan Abu Dawud, separating the hadiths that were considered weak from those that were authentic or hasan. The hadiths that were considered authentic or hasan were then collected by him in a separate book called "Sahih Sunan Abu Dawud". Al-Albani also provided his assessment and comments regarding the authenticity status of these hadiths. Through this research, the researcher aims to explore the method used by Sheikh al-Albani in defining the weak status of hadith. The research was carried out by conducting literature studies on several hadiths in the book, then observing and analyzing the methods applied by al-Albani. The results of this research show that the method applied by Sheikh al-Albani in analyzing hadith is in line with the method used by classical hadith scholars. When a hadith does not meet the criteria for an authentic or hasan hadith, al-Albani assesses it as a daif hadith.